KINDERGARTEN TEACHERS’ READINESS IN IMPLEMENTING KURIKULUM MERDEKA - Nursaputri, Esamada Rose; Sabat, Yuliyanto (Academy of Education Journal, 2023)
In order to address the education crisis, the government implemented Kurikulum Merdeka. Teachers must be able to adapt to changes in the curriculum in order for curriculum implementation to work smoothly. This study was conducted to get a knowledge of teacher readiness in implementing new curriculum, particularly in kindergarten schools. This research includes a type of descriptive research with a qualitative approach. To identify readiness, interviews were conducted towards teachers in TK Cendekia 2 Sidoarjo. According to the findings of the interviews, teachers are ready to implement kurikulum merdeka. Yet, there is still lack of awareness of the curriculum structure, and there is still a need of training about lesson plans preparation and teaching modules creation. They still don't have a clear concept of why it should be implemented. They also claimed requirements in trainings and times to understand how to integrate advanced technology into learning process.